Effect of Calligonum Comosum on Ovarian Histology of Polycystic Ovary mouse model - L Amini; N Tehranian; M Movahedin; F Ramezani Tehrani (Institue of Medicinal Plants, ACECR, 2015)
Background: Increased oxidative stress in women with polycystic ovary syndrome attracted attentions to antioxidant treatments. Calligonum Comosum is a planet with antioxidant propertis. Objective: This study aimed to investigating Calligonum effect on polycystic ovarian histology of polycystic ovary mouse model. Methods: Thity two female NMRI mice with 25-30 gr weight and 8 weeks age were investigated. A single dose of estradiol valerate (40 mg/kg; im) was used for induce polycystic ovarian morphology. Calligonum Comosom extract (20 mg/kg/ week; ip) was injected for 4 consequent weeks. In sham group, only DMSO was used. After 4 weeks, blood and histological samples were prepared to study. Results: There was no significant effect of 20 mg/kg Calligonum on polycystic ovarian morphology mouse model. Conclusion: The effect of other doses of Calligonum Comosum on fertility or adverse effect of this planet need to be more investigated.